Requirements and Value Elicitation for a High-Fidelity Pelvic Floor Simulator for Physiotherapists: Mixed Methods Study - Yael Zekaria; Antonia Tzemanaki; Jonathan Rossiter (JMIR Human Factors)
Abstract BackgroundPhysiotherapists lack training opportunities for repeated practice of pelvic examinations for the identification of pelvic floor disorders (PFDs), leading to low confidence in the clinical setting. Pelvic simulators exist and are a valuable supplement to the medical curriculum, yet none demonstrate pelvic floor muscle (PFM) function or dysfunction. To design effective simulators, an assessment of end-user requirements is essential. ObjectiveThis study aimed to elicit physiotherapists’ needs and requirements for a high-fidelity PFM simulator and the associated use cases. MethodsThis study followed a mixed methods design by collecting qualitative and quantitative data from a web-based survey. Quantitative data were analyzed using descriptive statistics and differences between demographic groups were calculated using 2-sample Kolmogorov-Smirnov 2-sided tests. Qualitative data were analyzed using thematic analysis. ResultsIn total, 66 physiotherapists completed the survey. The most common suggested use cases of the simulator were for training and professional development (56/66, 84.9%), and patient education (48/66, 72.7%). Pelvic organ prolapse and muscle tone function and dysfunction were identified as the most useful PFDs for the simulator to demonstrate. Positional tracking and force sensing were considered important features and there was a preference for a generic over a pathology-specific or patient-specific simulator. A total of 3 themes emerged through the qualitative analysis: prioritizing patient care; representing the variability in anatomy and PFDs for simulator realism; and consideration of the implementation, cost, and accessibility of simulators. ConclusionsThere is value in PFM simulators for physiotherapists for multiple use cases. Design recommendations include using realistic materials, demonstrating PFM dynamics, modularity to vary the complexity for different end-users, offering a range of feedback modalities for position and pressure sensing, and ensuring affordability and curriculum integration.